Reorganizing after the pandemic: A chance to energize physical activity promotion - comment on Hohberg et al. - Ryan Rhodes (Bern Open Publishing, 2022)
In this commentary on "What is needed to promote physical activity? - Current trends and new perspectives in theory, intervention, and implementation" I discuss my support for the many health, social, and economic benefits of moving more and sitting less as detailed by the authors. I discuss my agreement with the challenges of physical inactivity and sedentary behavior during the COVID-19 pandemic, and that while effective promotion initiatives founded on socioecological whole system approaches seem most logical, the role of individual is still essential for downstream uptake of physical activity. Like the authors, I include my support for the testing, development, and assumptions underlying dual-process theories using real time data-capture, in addition to more sophisticated longitudinal dynamic modeling to translate findings into just-in-time intervention approaches. In addition, however, I highlight it is still important for researchers and practitioners to focus on the role of reflective factors, such as building strong intentions to engage in physical activity, and subsequent self-regulation skills to translate these intentions into action. Furthering our understanding on the distinctions between initiation and maintenance of movement behaviors is important to advance theory and practice and the role of apex-system variables such as self- and social identity may hold considerable utility in physical activity science.  I suggest that finding meaning in movement behaviors beyond exercise is critical to reorganizing and reenergizing after the pandemic to promote physical activity.